Methodologies of Price Indices in Transition Countries - Zieschang, Kimberly (Washington, D.C. : International Monetary Fund, 1995)
Since late 1991, the IMF Statistics Department has conducted a program of technical assistance on consumer and producer price measurement and index compilation for the countries that have emerged from the former Soviet Union. These are countries whose economies are in various states of transition from centrally planned to market organization, and face special difficulties in developing price indices meeting international methodological guidelines for use in setting and monitoring the progress of macroeconomic policy. This paper describes and summarizes the findings of this technical assistance work with transition economies over the past four years, and the methodology developed by Fund experts to adapt international guidelines to the prevailing economic conditions. The paper catalogs the measurement problems and issues for compiling consumer and producer price indices in the transition context, and also comments on the use of these price series in compiling constant price national accounts.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet